Sebuah Eksplorasi Faktor Internal dan Eksternal Prokrastinasi Akademik: Sebuah Studi Kasus - Mistaq Marlina Khusna; Satiningsih (Universitas Negeri Surabaya, 2026)
Academic procrastination is a common issue among students and often arises from a complex interplay of personal and environmental factors. Its impact extends beyond delayed assignments, influencing motivation, concentration, and overall academic performance. This study aims to explore the case of a high school student, AD, and describe the internal and external factors contributing to his procrastination. The research employed a qualitative case study method, with data collected through observation and semi‑structured interviews, then analyzed descriptively to identify recurring patterns. The findings reveal that AD’s procrastination is shaped by internal factors such as low learning motivation, weak concentration, poor self‑regulation, and a preference for practical activities over theoretical subjects. External influences include strained family dynamics, limited parental autonomy, the undisciplined habits of his twin brother, peer conformity, and insufficient school control. Together, these factors create a multidimensional pattern of delay in academic tasks. This study highlights the importance of understanding procrastination not as a single‑cause behavior but as a phenomenon emerging from the interaction between personal tendencies and social environments. Abstrak Prokrastinasi akademik merupakan fenomena multidimensional yang sering muncul akibat interaksi antara kecenderungan pribadi dan lingkungan sosial. Penelitian ini bertujuan untuk mengkaji kasus seorang siswa SMA, AD, serta menggambarkan faktor internal dan eksternal yang memengaruhi perilaku prokrastinasinya. Penelitian menggunakan pendekatan studi kasus kualitatif dengan teknik observasi dan wawancara semi‑terstruktur, kemudian dianalisis secara deskriptif untuk menemukan pola yang berulang. Hasil penelitian menunjukkan bahwa prokrastinasi AD dipengaruhi oleh faktor internal seperti motivasi belajar yang rendah, kesulitan konsentrasi, regulasi diri yang lemah, serta preferensi terhadap aktivitas praktis dibandingkan mata pelajaran teoritis. Faktor eksternal meliputi dinamika keluarga yang kurang harmonis, keterbatasan kebebasan dari orang tua, kebiasaan saudara kembar yang tidak disiplin, konformitas teman sebaya, serta kontrol sekolah yang belum efektif. Kombinasi faktor‑faktor tersebut membentuk siklus penundaan dalam tugas akademik, menegaskan bahwa prokrastinasi bukanlah akibat dari satu faktor tunggal, melainkan hasil interaksi berbagai dimensi.